COVID-19—Impact on DNR Orders in the Largest Cancer Center in Jordan - Shamieh, Omar (J Pain Symptom Manage, 2020)
The COVID-19 pandemic requires health care teams to rethink how they can continue to provide high-quality care for all patients, whether they are suffering from a COVID-19 infection or other diseases with clinical uncertainty. Although the number of COVID-19 cases in Jordan remains relatively low compared to many other countries, our team introduced significant changes to team operations early, with the aim of protecting patients, families, and health care staff from COVID-19 infections, while preparing to respond to the needs of patients suffering from severe COVID-19 infections. This paper describes the changes made to our “do not resuscitate” policy for the duration of the pandemic.